Study on Employee Motivation based on Maslow Hierarchy's of Needs in an Insurance Company - Ganesh S/O, Lechumanan (2011)
Employee motivation is a key to the overall effectiveness of an organization.Employee motivation is the level of energy, commitment, and creativity that a company's workers bring to their jobs.Maslow’s Hierarchy of Needs theory is vital for understanding human motivation, management training, and personal development. This research was to study on employee motivation based on the Maslow Hierarchy of needs in an insurance company. The objective of the study is to identify the relationship between physiological needs and employee motivation, to identify the relationship between safety needs and employee motivation, to identify the relationship between social needs and employee motivation, to identify the relationship between ego needs and employee motivation, to identify the relationship between self actualization and employee motivation and finally to identify the most influencing dimension of Maslow Theory on employee motivation. This research conducted on the insurance agents of Tokio Marine Life (Butterworth).180 questionnaires were distributed to the insurance at the office entrance and 133 questionnaires collected successfully.Using the Maslow Hierarchy of Needs, this study asked the insurance agents to complete a survey to express their perception on the company and also their satisfaction and intentions towards working at Tokio Marine Life.Therefore, the employee’s motivation level can be measured.Pearson Correlation analysis pointed significant level of the independent variables with dependent and dependent variable.Multiple Regressions indicates the most influencing dimension of the Maslow Hierarchy of Needs on employee motivation.Possible interpretations, limitations, and implications for marketing specialized are conversed.